Testing Design Bioethics Methods: Comparing a Digital Game with a Vignette Survey for Neuroethics Research with Young People. Issue 1 (2nd January 2023) - Lyreskog, David M.; Pavarini, Gabriela; Jacobs, Edward; Bennett, Vanessa; Mawdsley, Geoffrey; Singh, Ilina
Abstract: Background: Over the last decades, the neurosciences, behavioral sciences, and the social sciences have all seen a rapid development of innovative research methods. The field of bioethics, however, has trailed behind in methodological innovation. Despite the so-called "empirical turn" in bioethics, research methodology for project development, data collection and analysis, and dissemination has remained largely restricted to surveys, interviews, and research papers. We have previously argued for a "Design Bioethics" approach to empirical bioethics methodology, which develops purpose-built methods for investigation of bioethical concerns. In this paper we compare a research tool created using a design bioethics approach to a "methods-as-usual" approach in empirical bioethics. Methods: Our study compared dimensions of engagement with a digital game we created, called "Tracing Tomorrow, " to a standard vignette survey. The two tools investigated the same subject matter, digital phenotyping for mental health, in a sample of 301 UK adolescents. Results: Participants who played the game reported a greater sense of presence, emotional engagement, cognitive absorption, and mental health ethics insight, compared to participants who completed the vignette survey. Perceived authenticity and curiosity/motivation to learn more was equivalent for both methods. Conclusion: The results of this study highlights the importance of purpose-built methodology for empirical bioethics research.